2013
DOI: 10.1080/14999013.2013.846950
|View full text |Cite
|
Sign up to set email alerts
|

Do the Static-99 and Static-99R Perform Similarly for White, Black, and Latino Sexual Offenders?

Abstract: The Static-99 is the most widely used sex offender risk assessment measure in the world, but predictive effects for the Static-99 have been relatively low in several U.S. samples, particularly in states with high levels of racial or ethnic diversity. The current study uses data from one of the largest predictive validity studies of Static-99 in the U.S. to examine whether Static-99 and Static-99R scores predict recidivism similarly for White (n = 912), Black (n = 411), and Latino (n = 588) offenders. Although … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 27 publications
7
37
0
Order By: Relevance
“…Low sexual offense recidivism rates have also been reported for Latino sex offenders by Varela et al (2013) and Hanson, Lunetta et al (2014). Moreover, we found that U.S.-born/Puerto Rican and other Latin American sex offenders (i.e., non-U.S.-born) in our sample did not differ significantly from one another with regard to their respective sexual recidivism rates.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Low sexual offense recidivism rates have also been reported for Latino sex offenders by Varela et al (2013) and Hanson, Lunetta et al (2014). Moreover, we found that U.S.-born/Puerto Rican and other Latin American sex offenders (i.e., non-U.S.-born) in our sample did not differ significantly from one another with regard to their respective sexual recidivism rates.…”
Section: Discussionsupporting
confidence: 64%
“…However, our findings were consistent with, but slightly lower than, other studies involving Latino sex offenders in Texas (Varela et al, 2013) and California (Hanson, Lunetta et al, 2014). The scores we obtained for our sample could be influenced by a number of factors.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…and Hispanic, n = 588; Varela et al, 2013). They found poor to moderate discrimination of Static-99/R for violent sexual recidivism (i.e., any contact sexual offense) across different ethnic groups (AUCs of .57 for Hispanics, .59 for Whites, and .65 for Blacks) and no significant differences among the ethnic groups.…”
Section: Hispanic Sex Offenders In Californiamentioning
confidence: 95%
“…They found poor to moderate discrimination for violent sexual recidivism (i.e., any contact sexual offence) across different ethnic groups (AUCs of .57 for Hispanics, .59 for Whites, and .65 for Blacks) and no significant differences among the ethnic groups. No calibration analyses were performed (see Varela, Boccaccini, Murrie, Caperton, & Gonzalez, 2013). Hanson, Lunetta, Phenix, Neeley, and Epperson (2014) reported good predictive validity with 475 sex offenders under the parole system in California (AUC of .82 [.72, .92]) and overall good and similar discrimination across all ethnic groups (e.g., White, Black, and Hispanic; AUCs >.74).…”
Section: Previous Studies Evaluating Cultural Bias In Static-99r and mentioning
confidence: 99%